Dampak Negative Gadget Terhadap Prilaku Agresif pada Anak Usia Dini - Dwi Anisak Nurul Fitri (Institut Madani Nusantara, 2024)
Aggression is one form of inappropriate social learning in children, as this behavior can be detrimental to both the child and others. This research aims to describe aggressive behavior that occurs in early childhood. This research is a qualitative study with a case study approach and is described descriptively. Data collection techniques were conducted through observation, open interviews, and documentation studies. The sample in this study was one early childhood education student and one early childhood education teacher. The research was conducted at Pembina 4 Kindergarten in Pekanbaru. Data analysis in this study was carried out in several steps, including (1) preparing raw data; (2) coding; (3) code classification; (4) data interpretation; and (5) data presentation. Data validation used in this study included member checks and reflexivity. The results of this study explain that aggressive behavior in children varies widely in form and can become stronger if it appears in childhood and is not handled appropriately. Therefore, effective collaboration between parents and teachers is needed to address aggressive behavior in early childhood.